IDENTIFIKASI METODE PEMELIHARAAN BERKALA PADA SALURAN SEKUNDER (SDU) DAERAH IRIGASI RAWA DELTA AIR SUGIHAN KANAN DI DESA TIRTA MULYA - Mayang Sari; Anggi Purnama Sari Dewi (Rang Teknik Journal, 2026)
Swamp land ecosystems have significant potential as productive agricultural areas, but face challenges of excessive water inundation during the rainy season and extreme drought during the dry season, which impacts the reduction of planting intensity. This research aims to comprehensively examine the periodic maintenance methods of the Main Distribution Channel (SDU) of the Sugihan Kanan Delta Water Swamp Irrigation Area in Tirta Mulya Village, Ogan Komering Ilir Regency, and identify types of damage and effective repair methodologies. The research method uses a qualitative descriptive approach through field observation, in-depth interviews with stakeholders, literature study, and documentation during the period from February to June 2025. The research results identified three main categories of damage: massive sedimentation, proliferation of wild vegetation, and deterioration of embankment structures that caused a reduction in channel capacity to 60-70% of design capacity. Implementation of periodic maintenance includes equipment mobilization, precision measurement, sediment dredging, vegetation cleaning, and embankment reconstruction with dimensions of 11 meters width, 2 meters depth, and 3 meters berm width. This research concludes that systematic periodic maintenance can restore optimal function of swamp irrigation channels and recommends implementation of sustainable sedimentation control programs and strengthening community participation in operational and maintenance of irrigation infrastructure to support regional food security.Keywords: Periodic Maintenance, Swamp Irrigation Channel, Sedimentation, Swamp Irrigation Area, Sugihan Kanan